Bleeding diathesis coincident with chronic myelomonocytic leukaemia. Issue 11 (November 1991) - Heard, S E; Revell, P; Holland, L J; Hurdle, A D; Savidge, G F
Abstract : Two important haematological problems were found in an otherwise healthy 78 year old man: chronic myelomonocytic leukaemia; and a complex, acquired, hyperfibrinolytic bleeding disorder characterized by prolonged coagulation times, deficiency of coagulation factors V, X, and XI, anti-thrombin III and proteins C and S, with high concentrations of circulating tissue plasminogen activator, and low concentrations of plasminogen activator inhibitor. There may be a causal relation between the two conditions, with the peripheral blood monocytes mediating the hyperfibrinolytic process by the abnormal production of tissue plasminogen activator, though no previous description of a similar association has been reported.